Toxic Professional Relationship in Academic Settings: A Personal Reflection and Pedagogical Implication (International Journal of Education and Literature, 2025)
Toxic professional relationships—characterized by subtle exclusion, politicized decision-making, and emotional suppression—are a prevalent yet underexamined concern in academic institutions. This research emphasizes the psychological, pedagogical, and emotional repercussions for educators in situations characterized by workplace conflict, in contrast to prior studies that primarily examine structural factors. The study seeks to examine how educators perceive, interpret, and react to toxic dynamics, especially via reflective processes. We gathered data from three years of anonymized reflective journaling employing a qualitative, narrative-reflective methodology and conducted a theme analysis. Research highlights three main themes: the emotional effort needed to maintain professionalism despite feeling excluded, changes in teaching methods as a way to resist and find meaning, and how reflective practice helps teachers stay true to their teaching values. The analysis further demonstrates how gender and early-career status exacerbate susceptibility to toxic dynamics. The study prioritizes ethical contemplation as a transforming practice and a means of action instead of providing prescriptive solutions. Institutions should implement emotional intelligence training, equitable task allocation, and peer support mechanisms to cultivate more equal academic settings. This research advocates for a work culture founded on explicit performance expectations, mutual respect, compassion, and integrity in education, facilitating a deeper comprehension of teachers' authentic experiences in challenging school environments.